Food security and its impact on growth among Sri Lankan children under five during the economic crisis in 2022 - Dilini Vipulaguna; Harendra de Silva; Jagath Ranasinghe; Gitanjali Sathiadas; Gayan Udara Sampath; Amali Dalpatadu; Prasad Chathurangana; Maheeka Seneviwickrama; Guwani Liyanage (BMC Nutrition)
Abstract The recent economic recession has reportedly worsened food insecurity in Sri Lanka. We assessed food insecurity and its impact on the growth of children aged 6–59 months through a community-based, descriptive, cross-sectional study conducted in 2022. Food insecurity was measured using the Household Food Insecurity Access Scale, and anthropometric measurements (weight, length/height) were taken using standard techniques. Weight faltering was defined as inadequate or no weight gain (flattening) or a drop in weight gain, based on the trajectory of the weight curve over two points six months apart. Additionally, food insecurity, stunting, and wasting during crisis were compared with pre-crisis data. The study included 832 children, with half of the households experiencing moderate to severe food insecurity. One-fifth of the children showed growth faltering during the crisis, and 8.9% of those with growth faltering crossed one centile line (0.67 SD). Among children facing food insecurity, the rate of growth faltering had doubled, with the residential sector (i.e., estate) tripling the risk of weight faltering. The rates of food insecurity and growth issues were notably higher during the crisis compared to pre-crisis data. This study highlights the worsening food insecurity and its significant impact on growth faltering in children under five during the 2022 economic recession.